The Venceremos Brigade: North Americans in Cuba Since 1969. (1st December 2015) - Kavitha Iyengar
Abstract : The Venceremos Brigade is an 'anti-imperialist Education Project' that began its travel to Cuba in 1969 to support and learn about the Cuban Revolution. On Venceremos trips, North American volunteers offer aid to Cuban government projects while touring the island nation and learning about both Cuba and revolutionary ideals. Participants in the projects are involved for both personal and political reasons, offering a model for productive political relations born of hostilities. Although its story remains undocumented within histories of both the US Left and US-Cuban relations, by 2015, the group had sent more than 9, 000 North American activists to the island. Through reading newspapers from Cuba, Venceremos Press Publications in the US, and by listening to personal narratives, this article documents this important political education project that continues to model productive relations today.